Solifenacin versus posterior tibial nerve stimulation for overactive bladder in patients with multiple sclerosis - Majdinasab, Nastaran; Orakifar, Neda; Kouti, Leila; Shamsaei, Gholamreza; Seyedtabib, Maryam; Jafari, Mohammad (Frontiers in Neuroscience, 2023)
Overactive bladder is a common complication in multiple sclerosis (MS) patients that influence their quality of life. This study aimed to compare the effectiveness of solifenacin succinate (SS) and electrical posterior tibial nerve stimulation (PTNS) in MS patients with overactive bladder. In this randomized controlled trial study, 70 MS patients with overactive bladder were randomly divided into two groups. In group I (35 patients), patients received SS, and in group II (35 patients), patients were treated with PTNS. The mean (SD) age of the patients was 39.82 (9.088) and 42.41(9.175) for the drug group and the electrical nerve stimulation group, respectively. According to the results, the changes in urinary incontinence and suffering from micturition frequency per day in the two groups have statistically significant differences over time (P<0.001) so that the rate of urinary incontinence during 12 weeks in the treatment group, solifenacin exhibited a significant decrease versus the PTNS group, and patients expressed greater satisfaction with the reduction in the number of times they urinate during the day. Both treatment methods are effective in treating overactive bladder in MS patients, and in patients treated with SS, compared to patients treated with electrical PTNS, there is more satisfaction with reducing the number of times to urinate during the day and urinary incontinence for 12 weeks of study was observed.